Knowledge of Tenant Employees in Fire Emergency Response Efforts at Airport Terminals: A Study of Its Influence - Komalasari, Yeti; Louis Santi Adnyana Kunde, Ketut; Abdullah, Anton; Agung Ayu Mas Oka, I Gusti; Danim, Sudarwan (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Fires in transport terminals are a serious threat that can cause material loss, physical damage, and risk loss of life. Bali's I Gusti Ngurah Rai International and Domestic Terminal is one of the most important transport hubs, serving thousands of visitors every day. It is important for tenant employees operating within these terminals to have adequate knowledge in fire emergency management. The purpose of the study is to ascertain how tenant employee knowledge affects the management of fire emergencies at I Gusti Ngurah Rai Bali airport's domestic and international terminals. This study uses a type of quantitative research using the method of distributing research questionnaires through google form with tested using IBM SPSS version 25. The research sample was drawn using probability sampling technique by adding a margin of error of 5% to obtain a sample of 50 people. The results obtained Partially, the knowledge of tenant employees has a significant influence on overcoming fire emergencies, with a determination value of 0.613 or in the form of a percentage of 61.3%, and obtaining a significant value of 0.000